Plant and Vegetation Mapping - Pedrotti, Franco; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The book is concerned principally with geobotanical mapping. Geobotany is a broad science that deals with the study of species and of vegetation communities in relation to the environment; it includes other, perhaps more familiar sciences, such as plant geography, plant ecology, and chorology, and phytosociology (plant sociology). Geobotanical cartography is a field of thematic cartography that deals with the interpretation and representation, in the form of maps, of those spatial and temporal phenomena that pertain to flora, vegetation, vegetated landscapes, vegetation zones, and phytogeographical units. The production of a geobotanical map represents the last stage in a cognitive process that begins with observations in the field and continues with the collection of sample data, interpretation of the phenomena observed, and their appropriate cartographic representation; geobotanical cartography is closely tied to the concepts and scope of geobotany in general
Geobotanical Mapping and its Levels of Study -- Mapping Populations -- Mapping Synusiae -- Chorological Maps -- Mapping Vegetation -- Types of Vegetation Maps -- Examples of Vegetation Maps -- Mapping Systems of Dynamically Related Communities -- Phytogeographical Mapping -- Mapping Vegetation Zones and Belts -- Mapping Plant Biodiversity -- Applied Geobotanical Mapping -- Geobotanical Mapping in Italy -- Mapping Environments.
Keywords: Geography; Life sciences; Physical geography; Plant Ecology; Botany; Earth Sciences; Biogeosciences; Physical Geography; Plant Ecology; Plant Sciences